2009
DOI: 10.1623/hysj.54.2.247
|View full text |Cite
|
Sign up to set email alerts
|

Application of neural network and adaptive neuro-fuzzy inference systems for river flow prediction

Abstract: Appropriate outflow from a barrage should be maintained to avoid flooding on the downstream side during the rainy season. Due to the nonlinear and fuzzy behaviour of hydrological processes, and in cases of scarcity of relevant data, it is difficult to simulate the desired outflow using physically-based models. Artificial intelligence techniques, namely artificial neural networks (ANN) and an adaptive neurofuzzy inference system (ANFIS), were used in the reported study to estimate the flow at the downstream str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(48 citation statements)
references
References 31 publications
0
48
0
Order By: Relevance
“…The gradient descent with momentum and adaptive learning rate algorithm can train any network as long as its weight, net input, and transfer functions have derivative functions [43]. This method uses back-propagation to calculate the derivative of the performance cost function with respect to the weight and bias variables of the network.…”
Section: Gradient Descent With Momentum and Adaptive Learning Rate Bamentioning
confidence: 99%
“…The gradient descent with momentum and adaptive learning rate algorithm can train any network as long as its weight, net input, and transfer functions have derivative functions [43]. This method uses back-propagation to calculate the derivative of the performance cost function with respect to the weight and bias variables of the network.…”
Section: Gradient Descent With Momentum and Adaptive Learning Rate Bamentioning
confidence: 99%
“…In recent years, artificial intelligence (AI) computational methods, such as the neuro-fuzzy systems have been increasingly applied to environmental issues (Chau 2006;Gharibi et al 2012). The neuro-fuzzy systems are the result of the combination of neural networks and fuzzy logic (Zadeh 1965;Pramanik and Panda 2009). Adaptive neuro-fuzzy inference system (ANFIS) as a multilayer feed-forward network is capable of combining the benefits of both these fields and also uses Gaussian functions for fuzzy sets, linear functions for the rule outputs and Surgeon's inference mechanism and mainly has been used for mapping input-output relationship based on available data sets Nourani et al 2011;Subbaraj and Kannapiran 2010;Ullah and Choudhury 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, neuro-fuzzy has been used successfully for prediction of flow through rock-fill dams (Heydari and Talaee 2011), river flow (Nayak et al 2004(Nayak et al , 2005Pramanik and Panda 2009;Kisi 2010), suspended sediment estimation (Kisi et al 2008;Cobaner et al 2009;Mirbagheri et al 2010, groundwater vulnerability (Dixon 2005, groundwater quality problems (Lu and Lo 2002;Zhou et al 2007;Hass et al 2012;Rapantova et al 2012;Jang and Chen 2015), daily evaporation (Dogan et al 2010;KarimiGooghari 2012) and rainfall-runoff modeling (Chang and Chen 2001;Gautam and Holz 2001;Xiong et al 2001;Jacquin and Shamseldin 2006). However, little research has been undertaken to study the problem of groundwater quality using ANN and GIS.…”
Section: Introductionmentioning
confidence: 99%
“…In general, many studies have confirmed that PLS was one of the most efficient methods used for constructing reliable models in wide range of fields, including in the field of hyperspectral remote sensing (Nguyen and Lee, 2006). Adaptive neuro-fuzzy inference systems (ANFIS), which combine the aspects of a fuzzy system with those of a neural network, have been widely used in many fields because of its usefulness with complex nonlinear problems (Sharma et al, 2015;Jang, 1993;Paiva et al, 2004;Abbasi and Abouec, 2008;Mukerji et al, 2009;Pramanik and Panda, 2009;Yan, 2010); ANFIS has also been applied to the hyperspectral assessment of soil properties (Tan et al, 2014). Although it is difficult to make full use of hyperspectral data because of the restriction on the number of input variables, ANFIS may be a promising technique in the field of hyperspectral remote sensing.…”
Section: Introductionmentioning
confidence: 99%